Breastfeeding in patients with peripartum cardiomyopathy: clinical outcomes and physician counseling - Angelina Noll; Kris R. Kawamoto; Maya T. Dassanayake; Laura Leuenberger; Stephanie M. Spehar; Jenny Wu; Elizabeth Langen; Melinda B. Davis (BMC, 2024)
Abstract Background Peripartum cardiomyopathy (PPCM) is a form of heart failure occurring towards the end of pregnancy or in the months following delivery. Concerns regarding the role of prolactin (the polypeptide hormone responsible for lactation) driving the pathogenesis of PPCM have led experts to discourage patients from breastfeeding; however, limited clinical data exist. We sought to (1) determine whether lactation was associated with less cardiac recovery and (2) assess the counseling about breastfeeding given to patients at the time of their initial diagnosis. Methods Patients diagnosed with PPCM from 1999 to 2019 were identified through detailed chart review and demographic characteristics, comorbidities, outcomes, and lactation status were collected. Cardiac recovery was defined as left ventricular ejection fraction (LVEF) 55% or higher. A survey about breastfeeding and patient experience was administered by mail. Patients were only included in this analysis if definitive information about lactation status was documented. Results Of 220 patients with confirmed PPCM, lactation status was known definitively in 54 patients; of these, 18 (33%) had breastfed for at least 6 weeks and 36 (67%) did not breastfeed. There were no significant differences in the breastfeeding and non-breastfeeding groups related to baseline LVEF, age, race, gestational diabetes, smoking, hypertensive disorders of pregnancy, and medication treatments. Despite similar baseline LVEF at the time of diagnosis, there was no statistically significant difference in cardiac recovery based on lactation status. In a subset of patients with severe cardiac dysfunction at the time of diagnosis, there remained no significant differences in recovery based on lactation status. Of the 34 survey respondents, 62% were told not to breastfeed due to their diagnosis or concerns regarding safety of medications, and none were encouraged to breastfeed. Conclusion In this retrospective cohort, lactation was not associated with lower rates of myocardial recovery. Importantly, a majority of patients had received counseling that they should not breastfeed. Future studies of the role of lactation in PPCM are needed in order to better understand the impact of breastfeeding and improve patient counseling.